THE ROLE AND INFLUENCE OF THE MEDIA IN COVERING MIGRATION PROCESSES - ZOXITOVA, Nodira (International Journal of Psychosocial Rehabilitation, 2020)
It’s no secret that migration is one of the key issues in a globalized world. How media coverage of these processes can be influenced by migration in countries of destination or origin, especially through online publications. Regular media coverage of immigrants comes to the minds of people, and the way in which they are covered, the language, and the journalist’s approach are one of the main contributors to the emergence of negative or positive opinions on immigrants, and the key to shaping their streaks. is one of the factors. In some cases, media outlets act in accordance with the principles of journalism and ethics in their country or politics. The study found the Web site of The Sun and The Guardian of the UK, one of the most developed countries. Leading online publications of Uzbekistan - Kun.uz and Daryo.uz were selected from developing countries. Their articles on the topic of November 2019 were reviewed. Further clarification of the topic helped to monitor, analyze and discuss the views of immigrants on the Internet, and discussions with people on the subject.